STATE OF FORMATION OF HIGH SCHOOL STUDENT’S SOCIALLY SUCCESSFUL PERSONALITY: ANALYSIS OF RESEARCH RESULTS - Fedorchenko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article presents the problem of forming high school student’s socially successful personality that is extremely relevant in modern science and practice in connection with the many challenges of a globalized society. The aim of the article is to analyze the current state of formation of high school student’s socially successful personality in general secondary education based on data obtained from empirical research, which will be the basis for creating a modern scientific and methodological foundation for updating content, developing productive forms, methods, and technologies of formation of socially successful personality with further approbation in the educational process of general secondary institutions and out-of-school education. The methodology of the ascertaining stage of the research was developed, which was aimed at a comprehensive view of socially successful personality, assessment of the level of skills of successful personality, identification of key social skills of high school students, motivation of success and fear of failure, the role of student self-government as a component of school democratization, the role of gender in the formation of a successful personality of students, the priority of a healthy lifestyle, determining readiness for professional self-determination. According to the results of the methodology, conclusions were made on the identified problem areas in the formation of high school student’s successful personality, namely: external circumstances, low level of their life competence, lack of necessary knowledge and skills to build life, determine the purpose of life based on their abilities, social and personal capabilities, carry out professional self-determination in society, how to get out of difficult life circumstances, overcome mental tension and stress, inability to work in a team, defend one's own position. The conclusions emphasize that further search for a solution will focus on accentuation on scientific and methodological support for the formation of high school student’s socially successful personality in general secondary education and raising awareness of teachers about forms, methods and technologies; motivational aspect in methodical work with pedagogical collectives, increase of students’ motivation to be successful, encouragement to acquisition of qualities of the socially successful person in a society, establishing partnerships with general secondary education institutions, promoting the formation of high school student’s social competence. The practical significance of the article is that its materials can be used in the organization of educational work in institutions of general secondary education, out-of-school education, as well as for scholars, postgraduate students, university students.